The Sintering Behaviour of Fe-Mn-C Powder System, Correlation between Thermodynamics and Sintering Process, Manganese Distribution and Microstructure Composition, Effect of Alloying Mode - Hryha, Eduard; Dudrova, Eva (IntechOpen, 2011)
None